Case report: Transected Hickman catheter and its thrombotic occlusion in a patient with idiopathic pulmonary arterial hypertension—can a catheter replacement be avoided? - Sławiński, Grzegorz; Zieleniewicz, Piotr; Faran, Anna; Dąbrowska-Kugacka, Alicja; Kurzyna, Marcin; Kempa, Maciej; Daniłowicz-Szymanowicz, Ludmiła; Lewicka, Ewa (Frontiers in Cardiovascular Medicine, 2023)
A 25-year-old female with idiopathic pulmonary arterial hypertension (PAH), who had a Hickman catheter implanted for continuous intravenous epoprostenol infusion, was admitted to the clinic after inadvertently cutting the catheter with nail scissors during a routine dressing change. Approximately 7 cm of the external segment of the Hickman catheter remained intact, with the distal end knotted by paramedics. A decision was made to repair the damaged Hickman catheter. However, it was discovered that its lumen was completely occluded by thrombosis. Therefore, catheter patency was mechanically restored using a 0.035-inch stiff guidewire in a sterile operating theatre setting, under fluoroscopy guidance. Successful aspiration and catheter flushing were achieved. Continuity of the Hickman catheter was then restored using a repair kit (Bard Access Systems) as per the manufacturer's instructions, with no visible leakage thereafter. Epoprostenol infusion through the Hickman catheter was resumed 24 h later, and the patient was discharged in good general condition two days afterward.